Analysis of Goldman Applanation Tonometry with and without fluorescein among glaucomatous and nonglaucomatous patients attending Mzuzu Central Hospital in Malawi: A cross‐sectional study - Munyapa, Tryness; Mzumara, Thokozani; Ogbonna, Grace; Mvula, Augustine (Health science reports, 2023)
Background and Aim Goldman Applanation Tonometry (GAT), the gold standard of tonometry, is used without fluorescein in low‐resource settings. Nevertheless, corneal biomechanics differ among population groups. Purpose The aim of the study is to assess the relationship between GAT findings with and without fluorescein among glaucomatous and nonglaucomatous adults in Malawi. Methods This was a cross‐sectional quantitative study involving 22 glaucoma patients and 22 nonglaucoma patients at Mzuzu Central Hospital. We used a purposive sampling technique to select participants into the two groups. Next, we measured intraocular pressure using GAT with and without fluorescein. Then we entered the data into SPSS version 25. We employed the Wilcoxon test to make comparisons based on age and gender. We considered the value of p < 0.05 statistically significant. Results There is a statistically significant and strong positive correlation between nfGAT and fGAT among both glaucoma (r = 0.989, p < 0.001) and nonglaucoma (r = 0.955, p < 0.001). According to age, there is no significant difference in IOP value measured with nfGAT and fGAT for both glaucomas (p = 0.109) and nonglaucoma subjects (p = 0.076). However, significant differences were observed between nfGAT and fGAT mean IOP according to sex among both glaucomatous and nonglaucomatous subjects (p = 0.017 and p = 0.32, respectively). Conclusion The study suggests that the merits of intraocular pressure measured using GAT without fluorescein are not speculative, therefore the two techniques can be routinely used interchangeably in diagnosing and managing glaucoma.